1995
DOI: 10.1002/j.1460-2075.1995.tb07323.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans-kingdom T-DNA transfer from Agrobacterium tumefaciens to Saccharomyces cerevisiae.

Abstract: Agrobacterium tumefaciens transfers part of its tumour‐inducing (Ti) plasmid, the transferred or T‐DNA, to plants during tumourigenesis. This represents the only example of naturally occurring trans‐kingdom transfer of genetic material. Here we report that A.tumefaciens can transfer its T‐DNA not only to plant cells, but also to another eukaryote, namely the yeast Saccharomyces cerevisiae. The Ti plasmid virulence (vir) genes that mediate T‐DNA transfer to plants were found to be essential for transfer to yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
409
0
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 581 publications
(430 citation statements)
references
References 55 publications
9
409
0
12
Order By: Relevance
“…The largest subfamily, the conjugation systems, are found in most species of Gram-negative and Grampositive bacteria. These systems mediate DNA transfer both within and between phylogenetically diverse species, and some systems even deliver DNA to fungi, plants and human cells 2,[9][10][11][12][13] . Conjugation is an important contributor to genome plasticity, and therefore bacterial fitness under changing environmental conditions, as encountered during infection of the human host.…”
Section: The T4s Familymentioning
confidence: 99%
“…The largest subfamily, the conjugation systems, are found in most species of Gram-negative and Grampositive bacteria. These systems mediate DNA transfer both within and between phylogenetically diverse species, and some systems even deliver DNA to fungi, plants and human cells 2,[9][10][11][12][13] . Conjugation is an important contributor to genome plasticity, and therefore bacterial fitness under changing environmental conditions, as encountered during infection of the human host.…”
Section: The T4s Familymentioning
confidence: 99%
“…Agrobacterium has been used extensively to 315 transfer DNA to eukaryotic algae in the green algal lineage with subsequent chromosomal integration (29)(30)(31)(32). In contrast, to our knowledge, the only other example beyond our results of using A. tumefaciens to deliver DNA maintained as an episome in the recipient was with yeast (14). During conjugation from E. coli to diatoms, it remains unclear how the DNA-protein 320 complex is transported to the recipient nucleus once in the eukaryotic cell.…”
Section: Discussionmentioning
confidence: 91%
“…tumefaciens-mediated transfer of episomes to P. tricornutum We also tested whether plasmids could be delivered by A. tumefaciens to the P. tricornutum and if they were maintained as episomes after transfer. In plants, A. tumefaciens is primarily used as a vehicle for insertion of DNA into the native chromosomes, yet Bundock et al (14) observed that the majority of DNA transferred to yeast by A. tumefaciens was maintained 255 episomally when the 2µm replication origin was included on the shuttle plasmid. We created two vectors to test transfer and maintenance.…”
Section: Plasmid Construction and Conjugation Experiments: 100mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a tool is necessary to clarify the role of those different genes in the symbiosis (e.g., are new transport events switched on as a result of interactions between the symbiotic partners?). Recently, a transformation protocol for ectomycorrhizal fungi based on the capacity of Agrobacterium tumefaciens to transfer its T-DNA to fungal cells as it does to plant cells (Bundock et al 1995) was developed by Pardo et al (2002). This method represents an interesting alternative to the traditional protoplast-mediated transformation, as this protocol can be implemented on intact fungal hyphae, thus circumventing the need for making protoplasts, which is tedious, time-consuming, and restricted to a limited number of ectomycorrhizal fungal species.…”
Section: Introductionmentioning
confidence: 99%